INDICATORS OF THIGH RHEOGRAM IN PRACTICALLY HEALTHY YOUNG MEN AND YOUNG WOMEN OF DIFFERENT SOMATOTYPES - Gunas, I.V.; Serebrennikova, О.А.; Hmel, L.L.; Smolko, N.M.; Smolko, D.G. (World of Medicine and Biology, 2019)
Correct estimation of rheovasographic indicators is impossible without taking into account the age, gender and somatotype of the subjects. The purpose of the study is to establish in practically healthy young women and young men of different somatotypes, inhabitants of Podillia region of Ukraine, features of indicators of thigh rheogram. In 108 healthy young women and 103 young men, in the third generation of urban adolescents of the Podillia region of Ukraine, the rheographic parameters of the thigh were determined. Anthropometric examination was performed according to the scheme of V.V. Bunak (1941). The mathematical scheme of J. Carter and B. Heath (1990) was used to evaluate the somatotype of adolescents. The statistical processing of the obtained results was carried out in the “Statistica 5.5” license package using non-parametric methods of estimating the results. The most pronounced differences in thigh rheogram indices in young women of different somatotypes are set for temporal (higher values in the representatives of the mesomorphic somatotype of the ascending part and slow blood flow of rheogram) and derivatives (smaller values in the representatives of the mesomorphic somatotype of the average speed of fast and slow blood type values – the tone of all the arteries and the tone of the arteries of medium and small diameter) indicators, and young men – for amplitude measurements (smaller values in the representatives of the mesomorphic somatotype). In addition, in young women of different somatotypes, most of the amplitude and almost half of the derived thigh rheogram indicators are greater than in young men of the respective somatotypes; in young men of different somatotypes – more than half of the time (except for slow blood flow of rheogram) indicators.
Keywords: indicators of thigh rheogram; practically healthy young men and young women; somatotype; sexual differences